Existential intertext of J. Fowles’ novel “The Collector” - Ilinska, Nina (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The purpose of the paper is to outline the components of the existential intertext of J. Fowles’ novel “The Collector”; consider those aspects that remain outside / on the periphery of researchers' attention, focusing on the authenticity of Miranda’s image; identify semantic transformations of pretexts in the mentioned discourse; consider intertextuality and intermediality as the main methods of creating an existential intertext.The image of Miranda Grey, close to the “alter ego” of the writer, is considered as an intertextual-composite construct. We consider its existentiality to be the semantic dominant of an image that absorbs other discourses. It was found that Miranda as an authentic person is defined by a tendency to self-identification; the desire for freedom and transcendence in various dimensions; ability to individualize creative activity and thinking; awareness of personal mortality. The innovativeness of the existential personality created by J. Fowles, which is represented in the gender aspect of “female power” as a marker of its authenticity, is emphasized.J. Fowles’ skill in “balancing” between the external and internal in creating the existential intertext of the work, which is manifested in its figurative system, is proved. The author models the relationship between Miranda, Clegg and Peston as a rivalry for power and the girl’s struggle for the authenticity of the female personality against the “masculine dictate”. Interpretation of a number of situations (“persecutor – victim”; “teacher – student”, “Madonna – fornicatress”, “Higgins – Galatea”, pattern of “lost paradise”, illusory embodiment of fantasies such as “princesse lointaine”, etc.) shows a paradoxical convergence of these opposites of the same axiology.The implicit use of the technique of intertextuality (allusions, quotations) marks J.P. and Clegg as ambivalent characters, demonstrating their duality in the external / internal model. To create an existential intertext, J. Fowles uses different types of ekphrasis (implicit, attributive, imaginary), which perform characterological, metapoetic, aesthetic, symbolic and allegorical functions. Intertextuality (intermediality) promotes text production and generation of meanings.